Pengaruh Esg Disclosure dan Green Accounting Terhadap Profitabilitas Perusahaan Manufaktur yang Terdaftar di BEI - Anzly Ramadhani; Heny Triastuti Kurnia Ningsih; Muhammad Joni Barus (Universitas Islam Islam Sumatera Utara, 2026)
This study aims to analyze the effect of ESG Disclosure and Green Accounting on the profitability of manufacturing companies listed on the Indonesia Stock Exchange, both partially and simultaneously. Profitability is proxied by Return on Assets (ROA), ESG Disclosure is measured using the ESG Disclosure Index (ESGDI) based on the Global Reporting Initiative (GRI) Standards 2021, while Green Accounting is measured based on the Company Performance Rating Assessment Program in Environmental Management (PROPER). This study employs a quantitative associative approach, with the population consisting of manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Using purposive sampling, 32 companies were selected, resulting in 96 observations. Data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics Version 26. The results show that ESG Disclosure has a positive and significant effect on profitability, whereas Green Accounting has no significant effect on profitability. Simultaneously, ESG Disclosure and Green Accounting have a positive and significant effect on the profitability of manufacturing companies.